2007
DOI: 10.22358/jafs/74599/2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing maize grains and soyabean on rumen fermentation and development of Holstein bull calves

Abstract: A feeding trial using 12 Holstein bull calves (21±3 d) was conducted to investigate the effect of different processed maize grain and full fat soyabean included in the starter diets on their rumen fermentation and development. Three treatment starter diets contained different processed maize grain and soyabean: steam-fl aked maize and soyabean (SFMS), extruded maize and soyabean (EMS), and ground maize and raw soyabean (GMS). During 10-week trial, total rumen VFA concentration tended to be infl uenced by diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The development of rumen papillae could also be affected by the of dorsal papillae length for barley and ensiled maize grain feeding compared to calves fed dry maize diets. Zhang et al (2007) observed differences in papillae length (P<0.05) when feeding calves diets differing in the rate of ruminal starch degradation. state that compared to ground maize or whole maize grain, flaked maize improved the formation of rumen papillae length (P<0.05) when feeding calves diets differing in the rate of ruminal starch degradation.…”
Section: Coefficients Of Ruminal and Intestinal Digestibility Of Protmentioning
confidence: 84%
See 2 more Smart Citations
“…The development of rumen papillae could also be affected by the of dorsal papillae length for barley and ensiled maize grain feeding compared to calves fed dry maize diets. Zhang et al (2007) observed differences in papillae length (P<0.05) when feeding calves diets differing in the rate of ruminal starch degradation. state that compared to ground maize or whole maize grain, flaked maize improved the formation of rumen papillae length (P<0.05) when feeding calves diets differing in the rate of ruminal starch degradation.…”
Section: Coefficients Of Ruminal and Intestinal Digestibility Of Protmentioning
confidence: 84%
“…It was probably due to the higher ruminal concentration of ammonia-N as a result of more rapid protein degradation than in the other groups (Khan et al, 2007). Because various amounts of straw were found after slaughter in the calves rumen it can be presumed that keeping calves on straw bedding could have a certain effect on pH and VFA concentration (Zhang et al, 2007). The greater numerical values (P>0.05) for propionic and butyric acids and the lower C 2 : C 3 ratio found in calves fed the ensiled maize diet, especially in combination with barley (group BM S ), suggests a greater ruminal degradation of starch than fibre compared to the other groups.…”
Section: Coefficients Of Ruminal and Intestinal Digestibility Of Protmentioning
confidence: 96%
See 1 more Smart Citation